Король Матиуш Первый: повесть-сказка / Я. Корчак - Корчак Януш (Просвещение, 1991)
Экземпляры: БС (20170802) / Инвентарный номер: РТШ48566 / Сис.шифр: И(Пол) / Авт.знак: К 70 / ГРНТИ: 17 / ББК: 84(4/8)